(untitled) (PerCursos, 2024)
This article proposes a reflection on intellectuality based on knowledge production organized outside the Western standards, and that stems from a sacred locus of practices and rites in Afro-Brazilian religions, known as terreiro. The research method was based on an ethnographic approach and draws on an open interview carried out at the Ilê Asé Ologbo Ogum terreiro, with the collaboration of the Candomblé’s Iyalorixá (priestess of Candomblé religion) Dalzira Maria Aparecida Yaguña de Ogum, a very dark black woman – as she refers to herself – who defended her doctoral thesis at the age of eighty. From the provocative questions made to the Iyalorixá and her answers to these questions, an intellectual tension was observed that pervades the flow between academia and the terreiro. The formal institutionalized knowledge and the knowledge acquired through conceptions experienced in the African-derived religious practices, which has ancestry as the mainstay for understanding the world, were contrasted. Thus, the narratives were organized around the processes of identity and resistance, considering memory as a linkage to ancestral heritage that, in this article, is constituted by means of affection and family ties. Orality was highlighted as the means that preserves, through oral language, the ancestral memory that guides time and permanence of people of African-derived tradition. It emerged that the epistemological reason that develops the processes of intellectuality produced in the field of knowledge, philosophy and thought of black people in Brazil is based on concepts that stem from the African cosmology that passes through the subject’s condition of being.